2004
DOI: 10.1590/s0100-67622004000500017
|View full text |Cite
|
Sign up to set email alerts
|

Patogenicidade de Verticillium lecanii ao pulgão-do-pinus

Abstract: PATOGENICIDADE DE Verticillium lecanii AO PULGÃO-DO-PINUS 1RESUMO -Avaliou-se a patogenicidade do isolado IBCB 473 de Verticillium lecanii no pulgão-do-pinus Cinara atlantica (Hemiptera, Aphididae), inseto-praga em plantios de Pinus spp. O delineamento experimental utilizado foi o inteiramente casualizado, com cinco repetições por tratamento e cada repetição constituída de uma placa de Petri (9 cm de diâmetro) contendo 10 ninfas. Foram testadas suspensões de inóculo nas concentrações de 1,0 ´ 10 6 ; 0,5 ´ 10 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
3
4
0
1
Order By: Relevance
“…The highest percent mortality was observed after 10 days, while after 3 days, the mortality was the minimum. Almost similar results were reported by Loureiro et al (2004) who found an increase in mortality with the increase in time and concentration. Contrarily, Araujo et al (2009) reported (90%) mortality at the high concentration (10 7 spore/ml) of B. bassiana after 4.4 days.…”
Section: Resultssupporting
confidence: 88%
“…The highest percent mortality was observed after 10 days, while after 3 days, the mortality was the minimum. Almost similar results were reported by Loureiro et al (2004) who found an increase in mortality with the increase in time and concentration. Contrarily, Araujo et al (2009) reported (90%) mortality at the high concentration (10 7 spore/ml) of B. bassiana after 4.4 days.…”
Section: Resultssupporting
confidence: 88%
“…The maximal effect was recorded after eight days, while the minimal effect was recorded after two days. These results are similar to research that showed an increase in the effect with the increase in time and concentration [39].…”
Section: Discussionsupporting
confidence: 91%
“…All concentrations were effective for the control of aphids, but the highest concentration (1 × 10 8 conidia mL −1 ) caused the highest percentage mortality [38]. The research was conducted for the determination of the virulence of V. lecanii and its result showed that concentration of 1 × 10 8 conidia mL −1 had the best effect, with an 86% mortality rate of nymphal observed after five days of application [39]. It was also reported that at concentrations of 10 7 and 10 8 conidia mL −1 of V. lecanii, the maximum mortality rate of M. persicae was recorded as 100% after 12 days of application [40].…”
Section: Discussionmentioning
confidence: 99%
“…As 93, 86 and 79% mortality was found after 10 days of application at highest concentrations (1 × 10 8 conidia mL −1 ) of B. bassiana BB-72, B. bassiana BB-252, and L. lecanii V-4, respectively, while 94, 84, 80 and 78% mortality of aphids were caused after 10 days of application by fungal strain combinations of BB-72 (LC 50 ) + BB-252 (LC 50 ), BB-72 (LC 50 ) + V-4 (LC 50 ), BB-252 (LC 50 ) + V-4 (LC 50 ), and BB-72 (LC 33 ) + BB-252 (LC 33 ) + V-4 (LC 33 ), respectively. An experiment was conducted for the evaluation of pathogenicity of L. lecanii isolates and found that best concentration was 1 × 10 8 conidia mL −1 with 86% nymphal mortality observed after at five days of application [31]. These results also corroborate the conclusions of [32] who studied that maximum mortality was 100% recorded after 12 days of application (at 10 7 and 10 8 conidia mL −1 ) of L. lecanii bioassayed against 3rd instar nymphs of green peach aphid.…”
Section: Discussionmentioning
confidence: 99%